PEMBERDAYAAN KELOMPOK WANITA TANI MOJOREJO MELALUI INOVASI PRODUK TEH CELUP BUNGA TELANG (Clitoria ternatea) SEBAGAI MINUMAN HERBAL FUNGSIONAL - Indriati Meilina Sari; Ikromatun Nafsiyah; Muhammad Hakim; Kiky Nurfitri Sari; Andika Prawanto; Mutmainnah Mutmainnah; Kansa Dianti Putri; Paisal Ansiska (Universitas Mataram, 2026)
The Mojorejo Women Farmers Group (KWT Mojorejo Lestari) consists of 20 housewives from Mojorejo Village, Selupu Rejang District, Rejang Lebong Regency. Most members have a secondary education background and engage mainly in household activities and small-scale farming. Limited knowledge and skills in managing local resources have hindered the group from developing productive businesses. This Community Service Program (PKM) aimed to empower the Mojorejo Women Farmers Group through vocational training using a learning by doing approach by utilizing butterfly pea (Clitoria ternatea) as the basis for developing innovative functional herbal tea bag products. The program included socialization, technical training, processing demonstrations, and qualitative evaluation through observation, interviews, and focus group discussions. The results showed that the group members were able to process butterfly pea into herbal tea bags with four flavor variants (butterfly pea + lemon, ginger, lemongrass, and cinnamon). Drying using a dehydrator was proven to be more effective than traditional sun drying, producing better color, aroma, and bioactive content. The tea bag products have been introduced to families and the local community, receiving positive responses and showing potential as a local flagship product. This activity not only improved the participants’ technical skills but also enhanced their entrepreneurial motivation and strengthened the organizational capacity of KWT Mojorejo to sustainably manage local resource-based businesses.